Laparoscopic vs. Open Repeat Hepatectomy for Recurrent Liver Tumors: A Propensity Score–Matched Study and Meta-Analysis - Chen, Jia-Feng; Fu, Xiu-Tao; Gao, Zheng; Shi, Ying-Hong; Tang, Zheng; Liu, Wei-Ren; Zhang, Xin; Gao, Qiang; Ding, Guang-Yu; Song, Kang; Wang, Xiao-Ying; Zhou, Jian; et al. (Frontiers in Oncology, 2021)
Background: It remains unclear whether the short-term benefits of laparoscopic repeat hepatectomy (LRH) accrue to patients with recurrent liver tumors. The present study aimed to report our own center’s experience and perform a meta-analysis to evaluate the safety and feasibility of LRH in comparison with open repeat hepatectomy (ORH) for treating recurrent liver tumors. Patients＆methods: A propensity score-matched study was performed including 426 patients receiving LRH or ORH for recurrent hepatocellular carcinoma between January 2017 and December 2018. Surgical outcomes and perioperative inflammation-based markers, including monocyte-to-lymphocyte ratio (MLR), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII) were collected from medical records and analyzed. Additionally, a systematic literature review was performed to identify relevant studies in PubMed, EMBASE, Web of Science and Cochrane library databases up to October 1, 2020. Information including patient demographic, pathologic characteristics and short-term outcomes was extracted and analyzed using random- or fixed-effects models. Results: Of 68 LRHs, 57 were matched with an ORH finally. Our study demonstrated that LRH was significantly associated with less intraoperative blood loss (50 versus 100 ml; P＜0.001), lower rate of hepatic inflow occlusion (10.52% versus 33.3%; P=0.003), and shorter postoperative hospital stay (5 versus 6 days; P=0.001) after 1:1 propensity score matching (PSM). The operation time, rate of blood transfusion and postoperative complications were similar between the two groups. Moreover, all four inflammation-based markers were significantly lower in LRH group on postoperative day (POD) 1. In the meta-analysis, a total of 12 studies comprising 1315 patients receiving repeat hepatectomy met the selection criteria. Similar with our own study, the meta-analysis showed shorter hospital stay (SMD=-0.51, 95%CI:-0.79~-0.22, P＜0.001), less intraoperative blood loss (SMD=-0.79, 95%CI:-1.11~-0.47, P＜0.001) and lower rate of major postoperative complications (OR=0.35, 95%CI:0.19~0.66, P=0.001) in the LRH group. There was no difference in the field of overall postoperative complication and operation time between LRH and ORH groups. Conclusion: Compared with ORH, LRH results in relatively better surgical outcomes and faster postoperative recovery. It could be considered a feasible and effective option for the treatment of recurrent liver tumors.